Bystander activation of microglia by Brucella abortus-infected astrocytes induces neuronal death via IL-6 trans-signaling - Rodríguez, Julia; De Santis Arévalo, Julia; Dennis, Vida A.; Rodríguez, Ana M.; Giambartolomei, Guillermo H. (Frontiers in Immunology, 2024)
Inflammation plays a key role in the pathogenesis of neurobrucellosis, where glial cell interactions are at the root of this pathological condition. In this study, we present evidence indicating that soluble factors secreted by Brucella abortus-infected astrocytes activate microglia to induce neuronal death.Culture supernatants (SN) from B. abortus-infected astrocytes induce the release of pro-inflammatory mediators and the increase of the microglial phagocytic capacity, two key features in the execution of live neurons by primary phagocytosis, a recently described mechanism whereby B. abortus-activated microglia kills neurons by phagocytosing them. IL-6 neutralization completely abrogates neuronal loss. IL-6 is solely involved in increasing the phagocytic capacity of activated microglia as induced by SN from B. abortus-infected astrocytes, and does not participate in their inflammatory activation.Both autocrine microglia-derived and paracrine astrocyte-secreted IL-6 endows microglial cells with up-regulated phagocytic capacity that allows them to phagocytose neurons. Blocking of IL-6 signaling by soluble gp130 abrogates microglial phagocytosis and the concomitant neuronal death, indicating that IL-6 activates microglia via trans-signaling. Altogether, these results demonstrate that soluble factors secreted by B. abortus-infected astrocytes activate microglia to induce, via IL-6 transsignaling, the death of neurons. IL-6 signaling inhibition may thus be considered as a strategy to control inflammation and CNS damage in neurobrucellosis.